MH and societal stigma: Changing attitudes may be a solution. Issue 23 (10th June 2022) - Maxson, Benjamin
Abstract : Stigmas have been a large part of society for as long as can be remembered, involving the labeling, disempowering, ostracizing, excluding, discriminating and stereotyping of individuals. Society has both seen and perpetuated the mistreatment of individuals consciously and unconsciously, largely through lack of information and societal processes that normalize placing individuals in categories. This is a psychological process that enables the brain to be at rest, because it is easier to see things as black or white, good or bad, acceptable or unacceptable than to exert the mental effort to empathize with and see each individual as unique. I call this seeing in the gray vs. black and white thinking. It is crucial that society learn this way of seeing. The stigma process is a disservice to society as a whole because the dominant culture will not benefit from the unique contributions of these individuals in our social structures and the process will hinder the individual from acceptance, growth, opportunity and overall well‐being.